Pengembangan Instrumen Penilaian untuk Mengukur Critical Thinking Skill Materi Relasi dan Fungsi - Erni Ekafitria Bahar; Rosmiyati . (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2022)
The development of critical thinking skills assessment instruments for students of class VIII MTs on the subject of relations and functions as well as describing the quality of the instrument (validity, reliability, level of difficulty, discriminatory power) are the main objectives of this research. The development model refers to Tessmer's formative research with stages: (1) preliminary, (2) self-evaluation, (3) prototyping (expert reviews one-to-one, and small group), and (4) field test. The grid, performance test questions and critical thinking skills descriptions, as well as assessment rubrics are assessment instruments developed with characteristics that refer to the critical thinking skill indicators according to Facione (interpretation, analysis, evaluation and inference). The results showed: (a) the performance test and the description test had high validity; (b) the reliability category of the performance test and description test items is good; (c) Question number 1 on the performance test and description has an easy level of difficulty and item number 2 has a moderate level of difficulty; (d) The distinguishing power of item number 1 on the performance test and description is in the satisfactory category and item number 2 is in the very satisfactory category. The results of the study indicate that the category of research instruments developed for relation and function material has a quality that is feasible to use Keywords: Development, Assessment Instrument, Critical Thinking Skill